Apple I replica creation: back to the garage - Owad, Tom (Syngress Pub., 2005)
Computers like the Apple I are incredibly simple machines. Even if you have no experience with electronics, this book will teach you how to build your own replica of the Apple I, show you how to program it yourself, and introduce you to exciting ways to expand your Apple I to control lights, motors, and more.